English Language Teaching in Post-Genocide Rwanda: A Study of Teachers’ Observance of the Grice’s Cooperative Principle - Jean de Dieu Karasenga; Innocent Nkundabatware; Olivier Munyansanga (INTERNATIONAL JOURNAL OF EDUCATIONAL REVIEW, 2020)
The purpose of this paper is to report about how teachers of English in Rwanda implement Grice’s cooperative principle in their classrooms, the challenges they face while implementing it, and how they deal with those challenges. The study upon which this paper is based used survey questionnaires, observations, and interviews as methods of data collection. Grounded theory analysis was employed to make sense of the data. Research findings are articulated according to four maxims including quantitative maxim, qualitative maxim, maxim of relevance, and the maxim of manner. They include the fact that teachers struggle with teaching the prescribed curriculum, communicating with students in English, and teaching what is at their students’ learning level. The paper concludes by devising implications of the findings for policy and practice.